S121 Co-morbidity and Pneumonia Risk in COPD Patients: A Population Database Analysis of Primary Care Patients. (12th November 2015) - Williams, N; Coombs, NA; Rigge, L; Josephs, L; Johnson, M; Thomas, DM; Wilkinson, TMA
Abstract : Background: Co-morbidities are common in COPD and have been associated with poorer clinical outcomes. Furthermore, patients with COPD are at an increased risk of developing Community acquired pneumonia (CAP). We investigated the impact of concurrent co-morbidity on the risk of developing CAP, in a cohort of COPD patients identified from the Hampshire Health Record analytical database, a local NHS database containing anonymised primary and secondary care records. Methods: Patients defined as having COPD, had a diagnostic Read code (classification of clinical terms for electronic information coding) in their primary care record at any time prior to 1 st January 2010 and were aged ≥40 years at the start of the study period. Using clinician-coded diagnoses, CAP episodes which occurred over a 1-year period from the 1 st January 2010 were identified using Read and ICD-10 code lists and were defined as taking up to 70 days to resolve. Listed co-morbidities were based on coded entries at any time prior to 1 st January 2010. Results: Included were 6707 patients with a complete history in 2010 and valid data for all variables considered in the analysis. 55% of patients were men and 36% were current smokers, the mean age was 70 years. 189 patients (2.8%) had at least one CAP episode during 2010. Compared to patients without CAP, patients with CAP were more likely to have ischaemic heart disease (IHD p = 0.005), congestive heart failure (CHF p = 0.021), hypertension (p = 0.017), cerebrovascular disease (CVD p < 0.001), dementia (p < 0.001), and bronchiectasis (p = 0.001). Using logistic regression and controlling for potential confounders, CVD and dementia were independent risk factors for CAP (p = 0.009 and 0.007, respectively), while bronchiectasis trended towards significance (p = 0.073) (Table 1 ). Conclusion: In this large population database analysis, CVD and dementia were identified as being independently associated with an increased risk of CAP. Oro-pharyngeal dysfunction in CVD and use of sedative medications in dementia, may contribute to these findings. Further analysis of the complete cohort, over the full 5-year observation period will allow the formulation of robust conclusions about the important factors of CAP risk in COPD, including the impact of pharmacotherapy, blood markers and functional parameters.